The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1364/oe.474970
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically electrical/thermal-tunable perfect absorber for a high-performance terahertz modulation

Abstract: We present a high-performance functional perfect absorber in a wide range of terahertz (THz) wave based on a hybrid structure of graphene and vanadium dioxide (VO2) resonators. Dynamically electrical and thermal tunable absorption is achieved due to the management on the resonant properties via the external surroundings. Multifunctional manipulations can be further realized within such absorber platform. For instance, a wide-frequency terahertz perfect absorber with the operation frequency range covering from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In the THz and MW regions, the dielectric constants of VO 2 can be described using the Drude model 45 , 46 : where ε ∞ = 12 is dielectric permittivity at the infinite frequency, is the plasma frequency of VO 2 that dependent on conductivity, = 5.75 ×10 13 rad· s −1 is the collision frequency, = 3 ×10 5 S· m −1 , = 1.5 ×10 15 rad· s −1 , is the conductivity of VO 2 (Fig. 4d and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the THz and MW regions, the dielectric constants of VO 2 can be described using the Drude model 45 , 46 : where ε ∞ = 12 is dielectric permittivity at the infinite frequency, is the plasma frequency of VO 2 that dependent on conductivity, = 5.75 ×10 13 rad· s −1 is the collision frequency, = 3 ×10 5 S· m −1 , = 1.5 ×10 15 rad· s −1 , is the conductivity of VO 2 (Fig. 4d and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[18,19] Similarly, studies on aerogels composed of phase change materials exhibited switching behavior, but with a more limited tuning range. [13,14] For example, Chang et al reported RL tuned from −17 to −54 dB, corresponding to a modulation in absorption in the range from 98% to ≈100%. [28] In addition, the tuning often covered a relatively narrow band with frequencies mostly located in the microwave range instead of in the THz range.…”
Section: Redox-switchable Thz Propertiesmentioning
confidence: 99%
“…Switchable materials that can modulate the absorption or transmission of THz signals are useful for intelligent calibration targets, dynamic attenuators for THz optical circuits, and effective modulators for electromagnetic interference, as demonstrated by multiple simulation results. [13][14][15] Only a few materials have shown decent tunability in the THz range, [13,14,[16][17][18][19] despite significant research progress in electromagnetic absorbers. [20][21][22][23][24][25][26] Several of these systems focused on modulating THz properties via reflection rather than absorption, and often with limited tuning range.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Hence, in-depth studies on the versatile or frequency reconfigurable MS enter a new boom by combining metallic resonators and tunable materials. Considerable methods of regulation include but are not limited to temperature, [33,34] gravity field, [35] illumination, [36,37] and electric field. [38] For instance, Singh et al experimentally demonstrated and compared the thermal tuning of the fundamental inductive-capacitive resonance, where metals and superconductors are discussed, to active MS resonance tuning.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] Hence, in‐depth studies on the versatile or frequency reconfigurable MS enter a new boom by combining metallic resonators and tunable materials. Considerable methods of regulation include but are not limited to temperature, [ 33,34 ] gravity field, [ 35 ] illumination, [ 36,37 ] and electric field. [ 38 ] For instance, Singh et al.…”
Section: Introductionmentioning
confidence: 99%